Accelerating drug development in breast cancer: New frontiers for ER inhibition. (September 2022) - Ferraro, Emanuela; Walsh, Elaine M.; Tao, Jacqueline J.; Chandarlapaty, Sarat; Jhaveri, Komal
Highlights: New ER inhibitors show improved pharmacokinetics and pharmacodynamics compared to fulvestrant. Composition of the side chain of oral SERDs affects their efficacy for efficacy. Five oral SERDs are in phase III trials in the advanced setting and two in the adjuvant setting. New ER inhibitors/degraders under investigation: SERCA, CERAN, PROTAC, and SERM/SERD hybrid. Oral route and potency render the agents ideal endocrine backbone for combination therapies. Abstract: The estrogen receptor (ER) is an important driver in the proliferation, tumorigenesis, and progression of breast cancers, and targeting ER signaling at different levels is a successful strategy in the control of hormone receptor positive (HR+) breast cancer. Endocrine therapy has been the treatment of choice for HR+ breast cancer in the early and advanced stages with multiple agents, including selective estrogen receptor modulators (SERMS), selective estrogen receptor degraders (SERDs), and aromatase inhibitors (AIs), which vary in their mechanisms of action and pharmacokinetics. Combination strategies also employ cyclin dependent kinase 4 and 6 and phosphatidylinositol 3-kinase to maximize the benefits of endocrine therapy. This paper reviews the clinical development of SERDs and other novel ER inhibitors, as well as combination strategies to overcome mechanisms of ER pathway escape. It also assesses the advantages of newer oral ER inhibitors with increased bioavailability, improved therapeutic index, better administration, and increased efficacy, as well as discussing future directions in the field.